Desarrollo profesional en la Universidad Nacional: construcción de un modelo para los talleres pedagógicos - Díaz Obando, Evangelina (2004)
In the face of the changes of paradigm that have been emerging in the pedagogical practice; changes that take place on a daily basis in all educational contexts within the Universidad Nacional, it is necessary to give professors opportunities to make critical reflections on their pedagogical practices, focusing on the transformation of those practices in order to reach more quality in higher education. In several activities that foster professional development within the university it has been possible to identify scholars who, both individually and in joint efforts, make this kind of reflection. This strength must be magnified in all the university in order to have a holistic training of all the agents taking part in the institution's teaching-learning processes. This is why in recent years more opportunities have emerged to reconsider classroom work. As a result, these activities are now part of the institutional agenda. In addition, due to the process of reorganizing the school year, new spaces are opening up to discuss several aspects that will impact the new organization in one way or another. Reorganizing the new school year requires to construct a new pedagogical perspective that needs to give special importance to training and updating within the university. Under this framework, all the teaching agents—professors and students—achieve special relevance since learning processes are emphasized (instead of methodology per se, as it occurs when teaching practices are based on a traditional view of these processes).